Catalytic sulphonated PVA membranes for the synthesis of isoborneol from camphene - Machado, A (2012)
Catalytic PVA membranes sulphonated with sulphoacetic acid and crosslinked with succinic acid were prepared and used in the synthesis of isoborneol from camphene with high selectivities and conversions.